WALDO AS THE MEDIA TO TEACH ENGLISH TENSES - Andi Dian Rahmawan (Universitas PGRI Yogyakarta, 2016)
In language teaching learning, teaching takes place as the primary activity. However, information about people’s language ability can be acknowledged from a useful and necessary testing. This useful device is highly considered because having the knowledge of a language, which is one’s linguistic competence is different to using this knowledge in actual production, which is one’s linguistic performance. A test as a subset of assessment, in simple terms, is a method of measuring a person’s ability, knowledge, or performance in given domain (Brown, 2004:3). Component of keywords related to this definition can be seen as (1) method – a set of techniques, procedures, or items that requires performance of the test-taker, (2) measure – to measure general ability, (3) individual’s ability, competence and performance – to understand who the test-takers are and (4) domain – a sample that represents general competence.